Tata Kelola dan Perlindungan Hak Asasi Manusia di Era Globalisasi Investasi: Strategi dan Tantangan - Agustin Widjiastuti; Nafis Dwi Kartiko (Jurnal Hukum Lex Generalis, 2024)
This research highlights the imbalance between foreign investment growth and human rights protection in Indonesia. The main problem is the potential for human rights violations in investment activities, such as land conflicts and socio-economic impacts that harm local communities. The purpose of this study is to evaluate the policies and strategies implemented by the government to ensure that investment is in line with respect for human rights, and to identify obstacles that hinder the effectiveness of such protection. The results show that while foreign investment can drive economic growth, stricter regulations, active stakeholder engagement, and effective oversight are needed to prevent human rights violations. This approach is expected to create a fair and sustainable investment environment, while safeguarding social and humanitarian interests in the midst of investment globalization.